Using magnetic material to repulse electrons in Axxent eBT for skin preservation during early-stage breast cancer conservative intra-operative radiotherapy - Wang, Li; Wu, Jia-Ming (Journal of Contemporary Brachytherapy, 2021)
A miniature electronic X-ray source was employed in this study to deliver intra-operative radiotherapy (IORT) within breast lesions. A flexible magnetic material was used to reduce breast skin radiation damage. Total prescribed dose was 20 Gy at balloon surface, with breast tumor bed wrapped around balloon applicator. A flexible magnetic material, called ‘neodymium-iron boron’ (NdFeB) + alloy-49 was applied to cover lesion’s surface to preserve the skin and to reduce electron contamination raised from photon-induced low-energy electrons, with tissue less than 1 cm between applicator surface and breast skin. The reduction of electron contamination using NdFeB + alloy-49 with an applicator-skin distance of 20 mm, ranged from 7% to 10%, while with an applicator-skin distance of 10 mm for balloon volumes from 30 to 50 cm3, it ranged from 4% to 6% only. NdFeB + alloy-49 magnetic material was efficient in repulsing photon-induced low-energy electrons for skin preservation to compensate for deficiency of tissue over less than 1 cm gap between the surface of applicator and the breast skin.